2007
DOI: 10.1111/j.1540-8159.2007.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ischemia‐Modified Albumin in Relation to Pacemaker and Defibrillator Implantation

Abstract: Permanent pacemaker-defibrillator insertion is associated with myocardial ischemia and necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Results from recent in vitro work from our group support this hypothesis and suggest that the generation of reactive oxygen species can at least transiently modify the N‐terminal region of albumin to yield increased levels of IMA 8 . This mechanism may offer an alternative explanation to the interesting findings by Sbarouni et al 1 in patients undergoing pacemaker—defibrillator implantation.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Results from recent in vitro work from our group support this hypothesis and suggest that the generation of reactive oxygen species can at least transiently modify the N‐terminal region of albumin to yield increased levels of IMA 8 . This mechanism may offer an alternative explanation to the interesting findings by Sbarouni et al 1 in patients undergoing pacemaker—defibrillator implantation.…”
supporting
confidence: 63%
“…We read with interest the paper by Sbarouni et al 1 which showed that ischemia‐modified albumin (IMA) levels increase after permanent pacemaker—defibrillator implantation. IMA levels were higher at 6 and 48 hours after pacemaker implantation, compared to baseline.…”
mentioning
confidence: 99%
“…"Catecholamine overload" (ref. [27][28][29] or direct mechanical damage [30][31][32][33][34][35][36][37][38][39] during skiascopy of the heart (during pacemaker implantation) can be a marker of procedure complexity and may positively correlate with troponin levels 31 . Left ventricular failure 40 , right ventricular failure [41][42][43] , or the disparity between physiological degradation of the myocardium and insufficient elimination of its fragments (renal insufficiency) (ref.…”
Section: Methodsmentioning
confidence: 99%
“…A similar rate for the onset of troponin I elevation was described by Altin 32 after monitoring 30 patients subjected to implantations of different types of pacemakers. In a study by Sbarouni 33 , the possibility of myocardial injury during the introduction of passive electrodes was demonstrated. This work evaluated a group of 64 patients and found that after primo-implantation of various devices, both troponin I levels and ischemia-modified albumin (IMA) levels were elevated.…”
mentioning
confidence: 99%
“…We thank Dr. Roy et al for the interest in our recent paper 1 showing that ischemia‐modified albumin (IMA) levels increase during pacemaker and defibrillator implantation along with cardiac enzymes, implying ischemia, and subsequent necrosis in this setting. Indeed, to our surprise, we found no significant differences among the various subgroups (i.e., single vs dual lead, with or without coronary artery disease, short or long procedure); in all these subgroups IMA increased invariably.…”
mentioning
confidence: 99%